A qualitative study of lived experience and life courses following dam release flooding in Northern Ghanaian communities: Implications for damage and loss assessment. - Moses Asamoah; Mawuli Dzodzomenyo; Faustina Twumwaa Gyimah; Chengxiu Li; Linda Agyemang; Jim Wright (PLoS ONE)
Background Dams provide water for industrial, agricultural, and domestic use, particularly in arid regions. However, controlled dam releases due to heavy rainfall may affect downstream communities' livelihoods and life courses such long-term impacts may be omitted from damage and loss assessments. This study aims to assess the lived experiences and long-term consequences of dam release flooding for downstream populations, comparing these with the typical scope of a damage and loss assessment (DaLA). Methods This research was conducted in two flood-prone districts in the White Volta basin, Ghana, subject to dam spillage. Four Focus Group Discussions (FGDs) with community opinion headers, household heads, chiefs, local politicians, and institutional staff were conducted and analysed, alongside semi-structured interviews with twelve opinion leaders and disaster-related institutions. Results Flood-affected communities struggled to attract partners for marriage due to stigmatisation from flooding impacts. Women outside flooded areas rejected male members' marriage proposals, while communities offered young girls for marriage to wealthy men for greater financial security. Out-migration of female members to seek better livelihoods frequently led to divorce, subsequently affecting children's education and well-being. Participants reported long-term trauma from flood-related contact with dangerous wildlife, travel disruption, disease risk, livelihood loss, and accidents. Such life course events and long-term trauma would be omitted from a DaLA exercise. Conclusion Beyond its immediate impacts, flooding undermines family relationships and marriage, impairing children's education and traumatises affected communities. We recommend livelihood diversification programmes, psychological support and family counselling to address these long-term impacts, with expansion of DaLA's scope to underpin such support.